Parking management system using xilinx FPGA / S.Saliha S. Bahroma ... [et al.] - S. Bahroma, S. Saliha; Abdul M, N. A.; Rosli, Anis Diyana; Ismail, Nurlida (2012)
This project is to design and develop a system which has the capabilities to detect empty spaces in the parking lot and indicate the area with the availability of the remaining spaces. This system is applicable in most industries which include the operations of a car parking lot. The main purpose of this project is to upgrade the facilities and technologies in typical car parking system. The system uses FPGA (Field Programmable Gate Array) Chip as the main controller and processor. The system is programmed using VHDL language by implementing a finite state machine (FSM) to control the sequence of the program. The program consists of arithmetic sequence operation and registry to register the availability of the parking spaces. The system will have sensors in each of the parking spaces to detect the vacancies of the spaces. The system will calculate the availability of each parking and produce an arithmetic display using seven segment displays. Each of the parking spaces will also be equipped with a lighted indicator to show the vacancies of the parking spaces for visual searching of the vacant spaces. Hardware implementation of the system is using a Digilent Spartan 3 system board and a sensor circuit that will be interfaced with the system board.